2004
DOI: 10.2166/wst.2004.0441
|View full text |Cite
|
Sign up to set email alerts
|

Sewage-treatment under substantial load variations in winter tourism areas – a full case study

Abstract: The sewage-load variations in winter tourism areas are characterized by sudden increases--in the range of a factor two to three--within only a few days at the start and the end of the tourist season, especially at Christmas. The sudden load increases occur during periods of low wastewater temperatures, which is an additional demanding factor with respect to nitrogen removal. A full case study was carried out at WWTP Saalfelden, which is located near one of Austria's largest skiing resorts. The plant is designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…communities described in this study, considering that the hydraulic connection of the two systems creates a continuous crossinoculation, and that differences in community structure are pronounced and consistent over time. This raises the question as to how community structure and function of high-rate and low-rate systems are affected when a substantial amount of biomass is continuously transferred from one system to another, as is the case in the Hybrid ® process (Winkler et al, 2004). To exploit the full capacity of a two-stage STP, one may argue that it is essential that both stages have distinctly different microbial communities to be better adapted to the specific purpose of each stage.…”
Section: Resultsmentioning
confidence: 99%
“…communities described in this study, considering that the hydraulic connection of the two systems creates a continuous crossinoculation, and that differences in community structure are pronounced and consistent over time. This raises the question as to how community structure and function of high-rate and low-rate systems are affected when a substantial amount of biomass is continuously transferred from one system to another, as is the case in the Hybrid ® process (Winkler et al, 2004). To exploit the full capacity of a two-stage STP, one may argue that it is essential that both stages have distinctly different microbial communities to be better adapted to the specific purpose of each stage.…”
Section: Resultsmentioning
confidence: 99%
“…The first stage of the Hybrid plant is highly loaded and usually characterized with a very low sludge volume index (SVI). Previous experiences have shown that properties of sludge from the high loaded stage essentially determine the properties of second stage sludge and that the SVI of the second stage is low, as well (Winkler et al, 2004). In case of WWTP3, the SVI was actually higher than expected and ranged up to 200 ml/g.…”
Section: Sludge Characteristicsmentioning
confidence: 82%
“…Kampman et al (2012) developed a reactor in which methane is used as electron donor for denitrification. Winkler, et al (2004) provided a full study case dealing sudden sewage-load increases in one of Austria's largest skiing resorts. On the other hand, selecting efficiency bacterium in low temperature in also a hot spot (Gratia 2009;Woo 2012).…”
Section: Introductionmentioning
confidence: 99%